An Investigation of Uses of Digital Technology Assisted Teaching of Early Childhood Teachers: Case Study of Teachers at International Schools and Public Kindergarten Schools of the PEASO - Cochrane, Thiwa; Jiraro, Pongthep; Sonprasit, Jinda; Lumpikanon, Kanya; Pibool, Suwimol (ASEAN Journal of Education, 2023)
The purpose of this research was to investigate the benefits and level of usage of digital technology in the early childhood classroom. Early Childhood (EC) who were born later (BLC: Born Later Children) where surroundings more fully provided by digital technologies than a First Born Child (FBC), causes of the BLC perceives digital technologies smarter than the FBC. Therefore, the BLC has better creative thinking, ability, and competency development than the FBC (Caldeiro- Pedreira, Renés-Arellano, Castillo-Abdul, & Aguaded, 2022) at the same time the BLC is finished to be total dimensional growth to preach their future characteristics. In this way, early childhood student teachers (EC Teachers) must have digital technology competences leading to learning management processes or felicitating and responding ECSs’ attentions and needs. The objectives of this study were to (1) investigate competences of usage, usage level, bene ciary, technological problem, and obstacle of EC Teachers, and (2) to investigate competences of usage, usage level, beneficiary, technological problems and obstacles of EC teachers based on different ages, nationality, experience, school, frequency of usage, and objective. Data was collected by online questionnaire from EC teachers at ISs and PKSs of the PEASO, and then the quantitative data were analyzed by statistics. It was found that: (1) usage of digital technologies assisted teaching of EC teachers, teachers focused on objectives, competence, usage level of digital technologies assisted teaching. There was a statistically significant benefit of .05, (2) there was statistically significant difference at .05 of usage level of digital technologies assisted teaching of EC teachers, (3) there was statistically signific nt difference at .05 of usage level of digital technologies assisted teaching of EC teachers on objectives, competence, usage level of digital technologies assisted teaching, and beneficiary, and (4) there was statistically significant difference at .05 of usage level of digital technologies assisted teaching of EC teachers that frequency of use was different.